2017
DOI: 10.1007/s10461-017-1730-9
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Traumatic Events and Symptoms of PTSD Among South Africans Receiving an HIV Test

Abstract: We studied posttraumatic stress disorder (PTSD) among a community sample of 500 persons seeking an HIV test. The majority of participants (62.2%) indicated that they had experienced at least one index event that qualified for PTSD, even though a small proportion (5%) actually met the diagnostic criteria for the disorder. Of those who reported an index event, 25 (8.04%) met the diagnostic criteria for PTSD while 286 (91.96%) did not. On average about one third of participants who did not meet the criteria for P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 32 publications
(36 reference statements)
0
6
0
Order By: Relevance
“…In multivariable analyses adjusted for gender and clinic the prevalence of probable PTSD was significantly higher among those who reported experiencing PTEs during childhood (aPR 2.0 [95% CI 1.1, 3.3]), violent PTEs during adulthood (aPR 1.7 [95% CI 1.0, 2.7]), and the death [3,11]. A study of PWH in Tanzania found that PWH reported a mean of three lifetime PTEs [12,41].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In multivariable analyses adjusted for gender and clinic the prevalence of probable PTSD was significantly higher among those who reported experiencing PTEs during childhood (aPR 2.0 [95% CI 1.1, 3.3]), violent PTEs during adulthood (aPR 1.7 [95% CI 1.0, 2.7]), and the death [3,11]. A study of PWH in Tanzania found that PWH reported a mean of three lifetime PTEs [12,41].…”
Section: Resultsmentioning
confidence: 99%
“…Exposure to potentially traumatic events (PTE) is common among people with HIV (PWH) and more common among PWH compared to the general population [1][2][3][4]. PTEs can take many forms, occur throughout the life course, and include violent and non-violent events in which an individual is exposed to actual or threatened death, serious injury, or sexual violence [5].…”
Section: Introductionmentioning
confidence: 99%
“…Few studies examined the effect of mental disorders on suicide behaviors among PLWH [1], especially in sub-Saharan Africa where the burden of HIV is the highest. PLWH are five to eight times more likely to report suicidal behaviors following exposure to trauma, compared with the general population [11][12][13]. Likewise, among PLWH, users of psycho-active substances were three to seven times more likely to attempt suicide than non-users, while sleeping disorders increased the risk of suicide attempts by two to five times among PLWH [14].…”
Section: Variablesmentioning
confidence: 99%
“…In South Africa, the country with the largest number of individuals living with HIV (Simbayi et al., 2019), the prevalence of community violence and its psychological consequences, including PTSD, are high (Atwoli et al., 2013). Among both individuals seeking an HIV test and those living with HIV, traumatic events and symptoms of posttraumatic stress have been reported in nontrivial proportions (Kagee, Bantjes, et al., 2017; Martin & Kagee, 2011). Symptoms of posttraumatic stress may be experienced prior to an HIV diagnosis due to exposure to previous stressful events.…”
mentioning
confidence: 99%
“…Symptoms of posttraumatic stress may be experienced prior to an HIV diagnosis due to exposure to previous stressful events. For example, in a sample of 500 South Africans seeking an HIV test, 62.2% reported having experienced a traumatic event, 8% of whom met the criteria for PTSD (Kagee, Bantjes, et al., 2017). However, most studies conducted on PTSD in the context of HIV have recruited samples of participants who are already infected with HIV.…”
mentioning
confidence: 99%